Robotics In Agriculture (International Journal of Engineering and Computer Science, 2017)
Computer-based sensors and actuators such as worldwide positioning systems, appliance vision, and laser-based sensors have increasingly been incorporated into mobile robots with the aim of configuring independent systems capable of shifting operator activities in agricultural tasks. However, the incorporation of many electronic systems into a robot impairs its trustworthiness and increases its cost. Hardware minimization, as well as software minimization and ease of combination, is essential to obtain feasible robotic systems. A step forward in the application of mechanical equipment in agriculture is the use of fleets of robots, in which a number of expert robots collaborate to accomplish one or several rural tasks.